Experimental and numerical study of ultrasonic monitoring of hydraulic fracture propagation - Nabipour, Amin (Curtin University, 2013)
Hydraulic fracture monitoring is very useful to understand real-time fracture movement to ensure unwanted events. Active seismic monitoring of hydraulic fracture propagation was studied numerically and experimentally. A discrete element method code was used for modelling the interaction of seismic waves with a propagating hydraulic fracture. A true triaxial stress cell was modified to conduct hydraulic fracturing ultrasonic monitoring experiments. Different seismic events were analysed and compared to estimate fracture geometry in real-time.